A randomized, double‑blind clinical study to assess the antiplaque and antigingivitis efficacy of Aloe vera mouth rinse - Bathini Chandrahas; Avula Jayakumar; Anumala Naveen; Kalakonda Butchibabu; Pathakota Krishnanjaneya Reddy; Tupili Muralikrishna (Wolters Kluwer Medknow Publications, 2012)
Aims: To evaluate the efficacy of Aloe Vera mouth rinse on experimental plaque accumulation and gingivitis. Materials and Methods: In this randomized, controlled, and double-blind study, a total of 148 systemically healthy subjects were screened in the age group of 18-25 years. Finally, 120 subjects were requested to abstain from oral hygiene (tooth brushing) for 14 days and used a specially fabricated plaque guard. Following cessation of tooth brushing in the specified area, the subjects were randomly divided into Group A (test group) who received 100% Aloe vera, Group B (negative control group) who received placebo (distilled water), and Group C (positive control group) who received 0.2% chlorhexidine. The rinse regimen began on the 15 th day and continued for 7 days. Plaque accumulation was assessed by Plaque Index (PI) and gingivitis was assessed by Modified Gingival Index (MGI) and Bleeding Index (BI) at baseline (0), 7 th , 14 th , and 22 nd days. Results: There was statistically significant decrease in PI, MGI, and BI scores after the rinse regimen began in both Group A (test group) and Group C (chlorhexidine) compared with Group B. Mouth wash containing Aloe vera showed significant reduction of plaque and gingivitis but when compared with chlorhexidine the effect was less significant. Conclusion: Aloe vera mouthwash can be an effective antiplaque agent and with appropriate refinements in taste and shelf life can be an affordable herbal substitute for chlorhexidine.